PENERAPAN MODEL TEAM-ASSISTED INDIVIDUALIZATION (TAI) DENGAN GAYA PEMBELAJARAN VISUAL, AUDITORI, DAN KINESTETIK (VAK) UNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGAN PERSUASI PADA PESERTA DIDIK SMA NEGERI 1 RANCAEKEK - Julianto, Julianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2017)
Writing is activity for exercise think ability become more than creative, productive, and expressive. Writing need diligence for develop essay design with the best. Writing skil have to training continual because writing not simple. This study have for question respond: (1) how planning writing skil persuasive essay use application team-assisted individualization with the style learning visual, auditori, and kinesthetic on the student class X SMAN 1 Rancaekek, (2) how implementation writing skil persuasive essay use application team-assisted individualization with the style learning visual, auditori, and kinesthetic on the student class X SMAN 1 Rancaekek, (3) how result writing skil persuasive essay use application team-assisted individualization with the style learning visual, auditori, and kinesthetic on the student class X SMAN 1 Rancaekek. This study tested the three cycle. Based on the study results, cycle one value persuasive essay is 55,4. The cycle two value persuasive essay is 68,5, and cycle three experience raise value become 80,2. So, the learning persuasive essay use application team-assisted individualization with the style learning visual, auditori, and kinesthetic on the student class X SMAN 1 Rancaekek can support the raise study achievement for student.